Using the Demirjian method for estimating the dental age of children in Surabaya, Indonesia - Beshlina Fitri Widayanti Roosyanto Prakoeswa; Arofi Kurniawan; An'nisaa Chusida; Beta Novia Rizky; Anugerah I'zaaz Darmawan; Andini Kamilia Nur Aisyah; Aspalilah Alias (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: The Demirjian method is used in assessing the stages of growth and development of teeth to calculate a person’s estimated age. In 1973, Demirjian identified the eight stages of tooth growth and development and their respective criteria. Purpose: To analyze the validity of Demirjian’s method for estimating dental age among children aged 6–17 years old in Surabaya, Indonesia. Methods: From August–October 2020, 162 panoramic radiographs of patients aged 6–17 years were taken at the radiology department of Airlangga Dental Hospital. Data analysis was conducted using SPSS software for different tests, including a paired t test. Results: Using the Demirjian method, there was no significant dissimilarity between chronological age (CA) and estimated dental age (EDA) in the male group. However, a significant dissimilarity was found between CA and EDA in the female group. Conclusion: Demirjian’s method can be used as a tool for estimating the dental age of males age 6-17 years old in Surabaya.